2020
DOI: 10.1021/acsami.0c16144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkyl Chain Length on Charge Transport Property of Anthracene-Based Organic Semiconductors

Abstract: Anthracene, a simple planar building block for organic semiconductors, shows strong intermolecular interactions and exhibits strong blue fluorescence. Thus, its derivatives have a great potential to integrate considerable charge carrier mobility and strong emission within a molecule. Here, we systematically studied the influence of alkyl chain length on the crystal structures, thermal properties, photophysical characteristics, electrochemical behaviors, and mobilities for a series of 2,6-di­(4-alkyl-phenyl)­an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Moreover, it has been found that the balance of the intermolecular transfer integrals is gradually improved by increasing the alkyl chain length of the alkylated phenyl groups in 2,6-Ants. 38 Therefore, we further speculate that the introduction of alkylated phenyl or thiophene groups may beneficial for realizing low-anisotropy of mobility in BTBTs. The reason takes into consideration (1) the alkylated phenyl or thiophene groups are used to extend the molecular π conjugation and tune molecular packing, (2) the variations of the alkyl chain length may gradually adjust the R -value to balance the intermolecular charge transport properties.…”
Section: Resultsmentioning
confidence: 84%
“…Moreover, it has been found that the balance of the intermolecular transfer integrals is gradually improved by increasing the alkyl chain length of the alkylated phenyl groups in 2,6-Ants. 38 Therefore, we further speculate that the introduction of alkylated phenyl or thiophene groups may beneficial for realizing low-anisotropy of mobility in BTBTs. The reason takes into consideration (1) the alkylated phenyl or thiophene groups are used to extend the molecular π conjugation and tune molecular packing, (2) the variations of the alkyl chain length may gradually adjust the R -value to balance the intermolecular charge transport properties.…”
Section: Resultsmentioning
confidence: 84%
“…Besides the study of side chain polarity, the impact of different alkyl chain lengths on the properties of charge transport had also been investigated. [ 114 ] The results indicated that the mobility has an increasing tendency with shorter alkyl chain length, related to the ordered microstructures of the thin films and crystallinity of the materials.…”
Section: The Optimization Of Power Factormentioning
confidence: 99%
“…[ 18 ] Some PAHs derivatives have been widely studied in solar cells, light‐emitting diodes, organic photovoltaics, organic transistors, etc. [ 19 ] Since PAHs usually consist of multiple vibrational energy levels in short‐wavelength spectral region, [ 20 ] the investigation of PAHs‐on‐Al devices may pave the way to understand the influence of Al materials on molecular vibrational couplings, which would contribute to the further construction of efficient light‐emitting devices.…”
Section: Introductionmentioning
confidence: 99%